Methods for Preclinical Assessment of the Efficacy of Anticancer Medicines in vivo (Review) - M. L. Vasyutina; K. V. Lepik; M. S. Istomina; K. A. Levchuk; A. V. Petukhov; E. V. Shchelina; A. E. Ershova; O. N. Demidov; Ya. G. Toropova (Регуляторные исследования и экспертиза лекарственных средств)
INTRODUCTION. The main risk to the clinical translatability of preclinical results for anticancer medicinal products is posed by the difficulty of simulating clinical conditions in an experimental model. With only 5% of product candidates proving clinically effective, the search for new approaches to the preclinical development of anticancer medicinal products is currently an active area of research in medicine.AIM. This study aimed to provide methodological support for planning experiments with modelling of neoplastic processes through analysis and classification of the methods used in preclinical studies of the efficacy of anticancer medicinal products in vivo.DISCUSSION. This article reviews the development of animal tumour models and the selection of cell lines and their testing for tumourigenicity and viability on a step-by-step basis. According to the study results, imaging systems, vital staining, and fluorescence- and luminescence-based methods can be used to assess the efficacy of anticancer medicinal products in both solid tumour models and haematological malignancy models. The article presents a schematic representation of the main types of mouse cancer models. However, no single animal species is universally suitable for in vivo cancer modelling. Researchers selecting models and considering their advantages and disadvantages should pay special attention to the similarity of disease mechanisms in animal models and humans at the tissue and molecular level, keeping in mind the aims of their research.CONCLUSIONS. The results of this comparative analysis of methods for preclinical efficacy evaluation of anticancer medicinal products are essential for designing experimental studies and ensuring the reliability of the results obtained. Choosing the correct research method will increase the chances of obtaining experimental data that can be successfully translated into clinical practice.